Partisipasi Masyarakat Dalam Mempertahankan Budaya Gotong Royong Untuk Meningkatkan Pembangunan Di RT 03, RW 01, Pematang Gubernur - Alfarizi, Aldi; Hendriansyah, Weko; Marsanda, Marsanda; Sulistiani, Sulistiani; Wahyudi, Sampirman; Putra, Iswidana Utama; Susena, Karona Cahya; Suwarni, Suwarni (LPPM Universitas Dehasen Bengkulu, 2025)
Mutual Cooperation is a cultural value that plays a crucial role in building social solidarity and community cohesion. However, social and cultural developments in modern times have led to a decline in community participation in mutual cooperation activities in some areas. This study aims to analyze the level of community participation, the factors influencing it, and strategies to strengthen mutual cooperation in RT 03 RW 01 Pematang Gubernur. A descriptive qualitative method was used, with data collected through observation and documentation. Informants were purposively selected, including the neighborhood head, community leaders, and residents who both participate and do not participate. The results show that community participation in mutual cooperation remains fairly high, especially in communal work and public facility development, supported by a sense of social responsibility and solidarity. The main obstacles are busy work schedules, individualistic lifestyles, and lack of awareness among some residents. Regular meetings and the role of community leaders effectively increase participation and a sense of belonging. The study concludes that strengthening the culture of mutual cooperation requires raising collective awareness, empowering community leaders, and adjusting activity schedules to accommodate residents’ needs. These findings are important for maintaining communal values amid social and cultural dynamics in modern society.